Growth patterns and masses of the heads and necks of male and female giraffes. (11th January 2013) - Mitchell, G.; Roberts, D.; van, S.; Skinner, J. D.
Abstract We have analyzed the growth patterns of the head and neck of 65 male and 71 female giraffes from two different populations of giraffes, and also the dimensions of 19 different components of the head and neck in 8 female and 13 male giraffes, to establish if they showed sexual dimorphism and if sexual selection for a weapon was a possible origin of the long neck of giraffes. We found that in both genders, the rate of increase in head mass was hypoallometric with respect to body mass. The rate of increase in neck length was similar in both genders and faster than the rate of increase in body mass. Increases in neck mass tend to be isometric relative to increases in body mass in both genders before puberty (c. 650 kg body mass in male and 700 kg in female giraffes), but in giraffes of greater body mass increases in neck mass are iso‐ to hyperallometric in both genders, with final neck, body and head mass being greater in male giraffes. The only significant gender difference we found for the dimensions of the 19 different head and neck components was that ossicones and skulls were heavier in mature male than in mature female giraffes, but increases in skull mass did not alter the growth pattern of head mass significantly. These data suggest that the morphology and growth patterns of the heads and necks of male and female giraffes are similar, that sexual dimorphism of the head and neck is minimal and can be attributed to secretion of sex steroids. We have concluded that there is no evidence that sexual selection was a factor in the evolution of giraffe morphology and that the long neck of giraffes did not evolve as a weapon in males. The more likely selective advantage of a long neck was improvement of access to high‐level browse.